Algorithms of turbulance detection with weather radars - Авер’янова, Ю.А.; Прокопенко, І.Г.; Прокопенко, К.І.; Яновський, Ф.Й. (Proceedings of National Aviation University (archive), 2012)
Algorithms of turbulence detection in the clouds and precipitation with radars were considered. Example of incoherent airborne radar with use of experimental data and statistical modeling was given to demonstrate advantages of adaptive algorithms. It was shown, that the adaptive algorithms can be used in combined Doppler and Polarization radars. It is important for flight when weather conditions are dangerous.